Про можливість автоматичного укладання термінологічних словників за фаховими текстами - Лазарєва, О. (Лексикографічний бюлетень, 2006)
The paper suggests an approach to creation of the vocabulary of terminological dictionaries. Word combinations of definite grammar structures being automatically extracted from the texts of some domain and arranged in a frequency list may constitute the basis for a terminological dictionary. The obtained vocabulary will be excessive and should be edited by an expert.